(3GdfGSN hGdefShNs - (3Gdbej, GdTjN GdUOhb, GHf HGHhjg Gdbej, eMeO Hf Ydj Hf GdMSjf, J (B381(3g` (B991(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg ecGaGJG dCaVGdg (B... (3aEf Pdc Ghd eG jLH Cf jHOC Hg aj Ydhe GdbQBf GdcQje, abO Qhj Yf CejQ GdeDefjf Cfg ONd eSLO GdchaI aQCi GHf OGH UGMH CHj ehSi GdCTYQj bO JMdb GdfGS Ydjg jSCdhfgs
(3BNQgG (B:s
(3BNQgG(B: (3agPg GdBjI efShNI HGdSfI hcnqfi ajgG HGdfSGA Yf PcQ GdfSGA hGdQLGd GdBjI hGddPGf jCJjGfgG efce GdBjI cGfJs
(3bGd UGMH GdPQjYI(B: (3EfgG cGedI aj ecJHI cGTa GdZWGA hGf fGSNgG CMeO Hf MHjH Rhjf HJGQjN (B1234(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 274s
(3GdPQjYI, L (B24: 9s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJaSjQ hYdhe GdbQBfs